2022
DOI: 10.1002/adma.202200474
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Bias in Molecule/Fe3GeTe2 van der Waals Heterostructures via Spinterface Effects

Abstract: a Curie temperature close to the room temperature and strong out-of-plane anisotropy. [7][8][9][10] Moreover, the magnetic properties of FGT are tunable, as they can be modified either electrically, applying a gate voltage [11] and a large electrical current, [12] or through magnetic proximity effects. [13][14][15][16] In particular, when interfaced with antiferromagnetic layered materials, FGT displays an increased coercivity and exchange bias, [13][14][15][16] which are the prototypical manifestation of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…Bulk vs Monolayer Limits. EB in 2D materials is detected by various means such as measuring the magneto-optic Kerr effect, 25,26,30 the anomalous Hall effect, 23,24,27,29,31 or the reflectance magnetic circular dichroism. 24,26 The large area of the samples produced by MBE allows for direct magnetization measurements of the samples by a SQUID magnetometer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bulk vs Monolayer Limits. EB in 2D materials is detected by various means such as measuring the magneto-optic Kerr effect, 25,26,30 the anomalous Hall effect, 23,24,27,29,31 or the reflectance magnetic circular dichroism. 24,26 The large area of the samples produced by MBE allows for direct magnetization measurements of the samples by a SQUID magnetometer.…”
Section: Resultsmentioning
confidence: 99%
“…EB in 2D materials is detected by various means such as measuring the magneto-optic Kerr effect, ,, the anomalous Hall effect, ,,,, or the reflectance magnetic circular dichroism. , The large area of the samples produced by MBE allows for direct magnetization measurements of the samples by a SQUID magnetometer. These measurements are accompanied by a study of electron transport in GdSi 2 films (see Methods for technical details).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the properties of 2D FGT is still in the preliminary stage, and further studies are required. For example, the exchange bias (EB) originating from the unidirectional pinning on the ferromagnetic/antiferromagnetic (FM/AFM) interface in vdW magnetic heterojunctions has huge potential applications in magnetic random-access memory, magnetic tunnel junctions, etc. By carefully designing the vdW stacking structure, Hu et al obtained an EB of 253 Oe at 10 K and observed an antisymmetric magnetoresistance in the FGT/MnPS 3 heterostructure.…”
Section: Introductionmentioning
confidence: 99%